A yolk-shaped core-shell catalyst Ni@HSS and preparation method thereof
By using the egg yolk-type core-shell catalyst Ni@HSS during the pyrolysis of paint hazardous waste, the dispersion and mesoporous structure of nickel nanoparticles in the hollow silica spheres is solved, and the catalyst is prone to carbon accumulation, sintering and inactivation is solved. , achieving efficient catalysis and stability at high temperatures, significantly improving the conversion rate and catalytic activity of toxic gases.
Patent Information
- Application Number
- CN202211635080.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-12-19
AI Technical Summary
Existing catalysts are prone to carbon accumulation, sintering and deactivation during the pyrolysis of paint hazardous waste, resulting in a decrease in catalytic activity and a decrease in conversion rate, especially under high temperature conditions.
Using the preparation method of the egg yolk-type core-shell catalyst Ni@HSS, the migration and aggregation of nickel particles is restricted by the highly dispersed and mesoporous structure of nickel nanoparticles in the hollow silica sphere, preventing sintering and carbon deposits, and combining with non-precious metal nano-nickel cobalt The alloy acts as the active center to improve catalytic stability and activity.
The high temperature stability and high conversion rate of the catalyst above 900°C were achieved, and the catalytic activity was almost not reduced for more than 50 hours, which significantly improved the catalytic pyrolysis efficiency of toxic gases such as formaldehyde and benzene in paint hazardous waste.
Smart Images

Figure CN116371407B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of core-shell catalysts, and in particular to an egg yolk-type core-shell catalyst for thermal decomposition of hazardous waste in paint production and chemical industry, which is suitable for treating toxic gases such as formaldehyde and benzene in the catalytic thermal decomposition industry of hazardous waste in paint. Background Art
[0002] During the painting process, some paint splashes outside the painted parts during the spraying operation, forming hazardous waste. At present, most companies absorb paint mist through circulating water in the paint spray room, condense it into paint waste residue, and then treat the waste residue. Paint waste residue is a hazardous waste, and improper treatment will cause great harm to the environment. Obtaining heat energy through thermochemical treatment is an effective way to treat paint waste residue harmlessly and recycle it, but how to control the sintering and carbon deposition of the catalyst under high temperature conditions during the thermochemical treatment process is a problem that needs to be considered when using this method.
[0003] The researchers conducted thermodynamic simulations for different reaction temperatures, pressures, feed ratios, and additional oxidants, and considered various carbon-forming reactions. The universal conclusions are: high conversion rates can only be achieved when operating at high temperatures and low pressures; minimizing the formation of carbon deposits is particularly important for the stable operation of the reaction process. The development of highly active, highly stable, deactivation-resistant, and economically viable catalysts is of great significance for the successful industrialization of thermal decomposition of paint waste. Many researchers have been working on the study of highly active and stable catalysts for the thermal decomposition of paint waste. Among the various types of catalysts, precious metals, transition metals, supported catalysts, spinels, perovskites, and mesoporous catalysts have been widely studied for this reaction.
[0004] Core-shell composite functional materials are multi-layer composite structural materials formed by a nano material encapsulating another micro-nano material through physical or chemical forces. There are many structures of core-shell materials in a broad sense, including hollow spheres, microcapsules, etc.
[0005] The shell structure of the core-shell catalyst has good stability, and its threshold effect can inhibit the agglomeration of core nanoparticles to a certain extent, thus making the catalyst have good stability. Specifically, it is reflected in: (1) preventing the sintering of active metals, thereby improving catalytic stability and resistance to carbon deposition; (2) the large contact interface area provided by the close contact of the core-shell materials strengthens the interaction between them; (3) if multiple active centers can be specially designed, the activity and selectivity can be improved; (4) the active sites can be integrated or modified by regulating the component structure of the core-shell, which can further improve the relevant performance of the catalyst. Nanomaterials with core-shell structures can not only effectively prevent the phenomenon of nanoparticles from being deactivated due to agglomeration, but also can further realize the integration of active reaction sites to adapt to complex catalytic reaction systems by changing the composition or structure of the core particles, or the composition and thickness of the shell layer.
[0006] The yolk-shaped core-shell structure is a new type of core-shell structure with a cavity between the core and the shell. Nanoparticles with the yolk-shaped core-shell structure have the characteristics of nanoreactors, which can provide many small independent microreactors, realize the dispersion of substrate molecules and increase the reaction rate, thereby improving the catalytic efficiency.
[0007] Patent document CN109225229A discloses a method for preparing a Ni@SiO2 core-shell structure catalyst, which is a core-shell structure catalyst with nickel nanoparticles as the core and silica balls as the shell; wherein the mass fraction of nickel is 3-6wt%, the size of nickel particles is 1-4nm, the mass percentage of silica is 97-94wt%, and the diameter of silica balls is 25-35nm, which is applied to the methane carbon dioxide dry reforming reaction and shows good activity. However, in the high-temperature catalytic process of this core-shell structure, the particle size of the metal particles is always difficult to control. As the temperature increases, the nickel particles will sinter and agglomerate, which greatly reduces the catalytic activity. When reacting above 800°C, the conversion rate of methane is reduced by more than 10%. In addition, the stability of the catalyst is poor. This is because as the reaction proceeds, the Ni site is covered by a dense silica shell layer, which will cause the loss of the number of active sites and gradually reduce its catalytic activity. Summary of the invention
[0008] In view of the problems that catalysts in the current catalytic pyrolysis process of hazardous paint waste are prone to carbon deposition, sintering, and deactivation, the purpose of the present invention is to provide an egg-yolk-type core-shell catalyst Ni@HSS and a preparation method thereof. The catalyst has the characteristics of stable catalytic effect, not easy to deactivate, not easy to deposit carbon and sinter, and high conversion rate.
[0009] In order to achieve the above object, the technical solution of the present invention is:
[0010] A method for preparing an egg yolk-shaped core-shell catalyst Ni@HSS of the present invention is characterized by comprising the following steps:
[0011] S1, Preparation of nickel nanoparticles
[0012] (1) uniformly mixing a nickel source and 1,2-hexadecanediol in a mixed solution of oleic acid, trioctylphosphine and oleylamine, and removing water and oxygen in the air in a N2 atmosphere to obtain a mixed solution A;
[0013] (2) heating the mixed solution A to 280-320°C and maintaining the constant temperature for 2-3 hours; then cooling the mixed solution to 80-100°C to obtain a mixed solution B;
[0014] (3) dissolving the mixed solution B in a solution consisting of oleylamine and borane-tributylamine complex, and keeping the mixture at 90-100°C for 2-3 hours to obtain a mixed solution C;
[0015] (4) adding ethanol to precipitate the mixed solution C, separating the solid product, and washing it with cyclohexane; drying to obtain metal nickel nanoparticles, and storing them under vacuum;
[0016] The nickel source is nickel acetylacetonate (II), and the concentration in the mixed solution A is 0.05-0.17 mol / L; the concentration of 1,2-hexadecanediol in the mixed solution A is 0.05-0.2 mol / L; the volume ratio of oleic acid, trioctylphosphine and oleylamine is (3-3.5): (4-5): 10, and the preferred volume ratio is 3.2: 4.6: 10; wherein the mass concentration of oleylamine is 60%-80%;
[0017] The molar ratio of the oleylamine to the borane-tributylamine complex is 1:(0.8-1);
[0018] S2, Preparation of yolk-type core-shell catalyst Ni@HSS
[0019] (5) cyclohexane, Solvay nonionic surfactant and ammonia solution are stirred and mixed in a reaction bottle to obtain a mixed solution D; the metal nickel nanoparticles are added to the mixed solution of tetramethyl orthosilicate, octadecyltrimethoxysilane and cyclohexane, and mixed evenly to obtain a mixture E;
[0020] (6) b. Add the mixture E to the mixed solution D and continue stirring at a temperature of 30-40°C for 60-90 min. Centrifuge to separate the solid, wash with ethanol and then vacuum dry.
[0021] (8) calcining the solid at 500-800° C. for 2-3 hours;
[0022] (9) reducing the calcined solid in a mixture of H2 and N2 at 800-850°C for 2-3h to obtain the egg yolk-type core-shell catalyst Ni@HSS;
[0023] The Solvay nonionic surfactant is a liquid nonionic surfactant, and its chemical name is nonylphenol polyoxyethylene ether, such as igepal CO-630 produced by Kuwai Chemical and ABEX AP470-Z produced by Rhodia.
[0024] Preferably, in the mixed solution D, the volume ratio of cyclohexane, Solvay nonionic surfactant and ammonia water is (25-30): (8-10): 1, preferably 25:8:1; the stirring time is at least 5 minutes;
[0025] Preferably, in the mixed solution E, the volume ratio of cyclohexane, tetramethyl orthosilicate and octadecyltrimethoxysilane is (25-30):(1-1.5):1, preferably 25:1:1; the mass concentration of the metal nickel nanoparticles in the mixed solution E is 1.0-1.5 mol / L.
[0026] Preferably, in step (6), the stirring temperature is 30° C. and the stirring time is 60 min.
[0027] Preferably, the calcination temperature is 800° C., the calcination time is 2 h, and the heating rate is 2-5° C. / min.
[0028] Preferably, in step (9), the volume fraction of hydrogen in the mixed gas is 5% to 15%, the flow rate of the mixed gas is 90 to 120 mL / min (preferably 100 mL / min), and the reduction time is 1.5 to 3.5 h.
[0029] The egg-yolk-type core-shell catalyst Ni@HSS prepared by the above method of the present invention is characterized in that a hollow silica sphere is used as a shell layer, nickel nanoparticles are used as the core of the egg-yolk-type structure in the shell, and the nickel nanoparticles are highly dispersed inside the hollow silica microspheres; the hollow silica spheres are provided with abundant mesoporous channels; wherein the mass fraction of nickel is 1 to 20wt%, the average size of the nickel particles is 2 to 10nm, the mass percentage of silica is 80 to 99wt%, and the average diameter of the silica spheres is 5 to 50nm; the channels on the hollow silica spheres are used to promote the reaction between the internal active sites and the external reactants, the nickel nanoparticles are completely confined in a zero-dimensional closed space by the shell layer, and are protected by silica, have a complete geometric confinement effect, and limit the migration and aggregation of the nickel particles to the greatest extent; the closed space structure does not have a free space for carbon deposition growth, has strong anti-sintering and anti-carbon deposition capabilities, and does not sinter above 900°C, which is much higher than the sintering temperature of other types of catalysts.
[0030] The egg yolk-shaped core-shell catalyst Ni@HSS of the present invention is used for catalytic pyrolysis of hazardous paint waste, especially for catalytic pyrolysis treatment of toxic gases such as formaldehyde and benzene.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The yolk-type core-shell catalyst Ni@HSS of the present invention uses non-precious metal nano nickel-cobalt alloy particles as the active center. Compared with precious metals, it greatly reduces the catalyst cost and is simple to operate, and has good development prospects in the industry. The catalyst prepared by the invention has good activity and excellent catalytic stability in the catalytic pyrolysis process of paint hazardous waste; due to the presence of mesopores, the yolk-shell structure has a higher specific surface area, a higher pore volume and a higher mass transfer efficiency. Compared with the Ni@SiO2 core-shell catalyst of comparative document 1, the Ni@HSS yolk-type core-shell catalyst prepared by the present invention has excellent catalytic activity even at high temperatures above 800°C, and the conversion rate of the reactants is above 90%; at the same time, the catalyst has excellent stability, and the catalytic activity decreases by less than 1% after more than 50 hours of reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a transmission electron microscopy image of the egg-yolk-type core-shell catalyst Ni@HSS of Example 1.
[0034] Figure 2 The XRD diagrams of the catalysts of Example 1 and Comparative Examples 1-2 are shown.
[0035] Figure 3 The catalysts of Example 1 and Comparative Examples 1-2 were used to test the conversion rate and catalytic stability of formaldehyde gas in paint micro-waste.
[0036] Figure 4 This is a thermal gravimetric test of the catalysts of Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0037] Those skilled in the art should recognize that the present embodiment is only used to illustrate the present invention, and is not used to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.
[0038] Example 1
[0039] A method for preparing an egg yolk-shaped core-shell catalyst Ni@HSS comprises the following steps:
[0040] S1, Preparation of nickel nanoparticles
[0041] (1) 1.54 g of nickel (II) acetylacetonate and 1.56 g of 1,2-hexadecanediol were mixed evenly in 6.4 mL of oleic acid (OAc), 9.2 mL of trioctylphosphine (top, 90%) and 20 mL of oleylamine (OAm, mass concentration of 70%), and water and oxygen in the air were removed in a N2 atmosphere to obtain a mixed solution A;
[0042] (2) Heat the mixed solution A to 300°C and keep the temperature constant for 2 hours; then cool it to 90°C to obtain a mixed solution B;
[0043] (3) quickly dissolving the mixed solution B in a solution consisting of 12.0 mL of oleylamine and 1.58 g of borane-tributylamine complex (BTB, 97%), and keeping the mixture at 90 °C for 1 h to obtain a mixed solution C;
[0044] (4) 50 mL of ethanol was added to precipitate the mixed solution C, and the solid product was separated and washed with cyclohexane three times; the solid product was dried in a vacuum oven to obtain metal nickel nanoparticles with an average size of about 5 nm, which were stored under vacuum.
[0045] S2, Preparation of yolk-type core-shell catalyst Ni@HSS
[0046] (5) 50 mL of cyclohexane, 16 mL of Solvay nonionic surfactant (Igepal CO-630) and 2.0 mL of ammonia solution were mixed in a three-necked flask and stirred for 10 min to obtain a mixed solution D; 3.0 mmol of metal nickel nanoparticles were added to a mixed solution of 2.0 mL of tetramethyl orthosilicate (TMOS, 98%), 2.0 mL of octadecyltrimethoxysilane (C18TMS, 90%) and 50 mL of cyclohexane, and mixed well to obtain a mixture E;
[0047] (6) Adding mixture E to mixed solution D, stirring at 30°C for 60 min; centrifuging to separate the solid, washing it with ethanol three times, and vacuum drying it at 100°C;
[0048] (8) calcining the solid at 800 °C for 2 h with a temperature increase gradient of 3 °C / min;
[0049] (9) The calcined solid was in situ reduced in a mixture of H2 (volume fraction 10%) and N2 (volume fraction 90%) at 800°C for 2 h at a flow rate of 100 mL / min to obtain the egg yolk-type core-shell catalyst Ni@HSS; wherein the mass fraction of nickel was 6 wt%, the average size of the nickel particles was 5 nm, the mass percentage of silica was 90 wt%, and the average diameter of the silica spheres was 30 nm.
[0050] Example 2
[0051] A method for preparing an egg yolk-shaped core-shell catalyst Ni@HSS comprises the following steps:
[0052] S1, Preparation of nickel nanoparticles
[0053] (1) 3.54 g of nickel (II) acetylacetonate and 1.56 g of 1,2-hexadecanediol were mixed evenly in 6.4 mL of oleic acid (OAc), 9.2 mL of trioctylphosphine (top, 90%) and 20 mL of oleylamine (OAm, mass concentration of 70%), and water and oxygen in the air were removed in a N2 atmosphere to obtain a mixed solution A;
[0054] (2) Heat the mixed solution A to 300°C and keep the temperature constant for 2 hours; then cool it to 90°C to obtain a mixed solution B;
[0055] (3) quickly dissolving the mixed solution B in a solution consisting of 12 mL of oleylamine and 1.58 g of borane-tributylamine complex (BTB, 97%), and keeping the mixture at 90 °C for 1 h to obtain a mixed solution C;
[0056] (4) 50 mL of ethanol was added to precipitate the mixed solution C, and the solid product was separated and washed with cyclohexane four times; the solid product was dried in a vacuum oven to obtain metal nickel nanoparticles with an average size of about 10 nm, which were stored under vacuum.
[0057] S2, Preparation of yolk-type core-shell catalyst Ni@HSS
[0058] (5) 50 mL of cyclohexane, 16 mL of Solvay nonionic surfactant (Igepal CO-630) and 2 mL of ammonia solution were mixed in a three-necked flask and stirred for 10 min to obtain a mixture D; 6.0 mmol of metal nickel nanoparticles were added to a mixture of 2 mL of tetramethyl orthosilicate (TMOS, 98%), 2 mL of octadecyltrimethoxysilane (C18TMS, 90%) and 50 mL of cyclohexane, and mixed well to obtain a mixture E;
[0059] (6) Add mixture E to mixed solution D and continue stirring at 30°C for 60 min. Centrifuge to separate the solid, wash it three times with ethanol, and dry it in vacuum at 100°C.
[0060] (8) calcining the solid at 800 °C for 2 h with a temperature increase gradient of 3 °C / min;
[0061] (9) The calcined solid was in situ reduced in a mixture of H2 (volume fraction 10%) and N2 (volume fraction 90%) at 800°C for 2 h at a flow rate of 100 mL / min to obtain the egg yolk-type core-shell catalyst Ni@HSS; wherein the mass fraction of nickel was 15 wt%, the average size of the nickel particles was 10 nm, the mass percentage of silica was 82 wt%, and the average diameter of the silica spheres was 30 nm.
[0062] Example 3
[0063] A method for preparing an egg yolk-shaped core-shell catalyst Ni@HSS comprises the following steps:
[0064] S1, Preparation of nickel nanoparticles
[0065] (1) 2.92 g of nickel (II) acetylacetonate and 1.56 g of 1,2-hexadecanediol were mixed evenly in 6.4 mL of oleic acid (OAc), 9.2 mL of trioctylphosphine (top, 90%) and 20 mL of oleylamine (OAm, mass concentration of 70%), and water and oxygen in the air were removed in a N2 atmosphere to obtain a mixed solution A;
[0066] (2) Heat the mixed solution A to 300°C and keep the reaction at a constant temperature for 2 hours; then cool it to 90°C to obtain a mixed solution B;
[0067] (3) quickly dissolving the mixed solution B in a solution consisting of 12 mL of oleylamine and 1.58 g of borane-tributylamine complex (BTB, 97%), and keeping the mixture at 90 °C for 1 h to obtain a mixed solution C;
[0068] (4) 50 mL of ethanol was added to precipitate the mixed solution C, and the solid product was separated and washed with cyclohexane for 4 times; the solid product was dried in a vacuum drying oven to obtain metal nickel nanoparticles with an average size of about 8 nm, which were stored under vacuum.
[0069] S2, Preparation of yolk-type core-shell catalyst Ni@HSS
[0070] (5) 50 mL of cyclohexane, 16 mL of Solvay nonionic surfactant (Igepal CO-630) and mL of ammonia solution were mixed in a three-necked flask and stirred for 10 min to obtain a mixed solution D; 9 mmol of metal nickel nanoparticles were added to a mixed solution of 2 mL of tetramethyl orthosilicate (TMOS, 98%), 2 mL of octadecyltrimethoxysilane (C18TMS, 90%) and 50 mL of cyclohexane, and mixed well to obtain a mixture E;
[0071] (6) Adding mixture E to mixed solution D, stirring at 30°C for 60 min; centrifuging to separate the solid, washing it with ethanol three times, and vacuum drying it at 100°C;
[0072] (8) calcining the solid at 800 °C for 2 h with a temperature increase gradient of 3 °C / min;
[0073] (9) The calcined solid was in situ reduced in a mixture of H2 (volume fraction 10%) and N2 (volume fraction 90%) at 800°C for 2 h at a flow rate of 100 mL / min to obtain the egg yolk-type core-shell catalyst Ni@HSS; wherein the mass fraction of nickel was 10 wt%, the average size of the nickel particles was 8 nm, the mass percentage of silica was 86 wt%, and the average diameter of the silica spheres was 30 nm.
[0074] Comparative Example 1
[0075] This comparative example 1 is a comparative example of Example 1, and the catalyst Ni / HSS is prepared as follows:
[0076] (1) Dissolve 1.54 g Ni(NO3)2•6H2O in deionized water and stir at 80°C for 10 min to obtain a nickel nitrate solution;
[0077] (2) 5.0 mL of tetramethyl orthosilicate (TMOS, 98%) and 5.0 mL of octadecyltrimethoxysilane (C18TMS, 90%) were fully mixed and stirred at room temperature for 10 min; then vacuum dried at 10 °C for 24 h to obtain solid HSS;
[0078] (3) The nickel nitrate solution was uniformly added dropwise onto the solid HSS, stirred for 10 min, and then vacuum dried at 100 °C for 12 h to obtain Ni / HSS; wherein the mass fraction of nickel was 6 wt %, the average size of the nickel particles was 8 nm, the mass percentage of silica was 90 wt %, and the average diameter of the silica spheres was 40 nm.
[0079] Comparative Example 2
[0080] This comparative example 2 is a comparative example of Example 1, and the catalyst Ni / SiO2 is prepared as follows:
[0081] (1) Dissolve 1.54 g Ni(NO3)2•6H2O in deionized water and stir at 80°C for 10 min to obtain a nickel nitrate solution;
[0082] (2) Add nickel nitrate solution dropwise onto commercial SiO2, stir for 10 min, and then vacuum dry at 100 °C for 12 h to obtain Ni / SiO2; wherein the mass fraction of nickel is 8 wt%, the average size of nickel particles is 8 nm, the mass percentage of silicon dioxide is 86 wt%, and the average diameter of silicon dioxide spheres is 50 nm.
[0083] Application Example 1
[0084] The three different catalysts of Example 1 and Comparative Examples 1-2 were characterized by XRD. Figure 2 As shown, compared with the catalyst Ni / HSS and the catalyst Ni / SiO2, the peak area of the catalyst Ni@HSS of the present invention is the smallest. This indicates that the Ni particles in the catalyst Ni / HSS and the catalyst Ni / SiO2 have grown significantly, while the Ni particles in the catalyst Ni@HSS have not changed significantly. Because the smaller the Ni particles, the higher the conversion efficiency, the catalytic efficiency of the catalyst Ni@HSS of the present invention is higher than the other two.
[0085] The three different catalysts of Example 1 and Comparative Examples 1-2 were subjected to thermogravimetric analysis. Figure 4 It can be seen that the catalyst Ni / SiO2 showed the most obvious weight loss phenomenon (21.9%), which indicates that it has the most serious carbon deposition, which is also the main reason for the decrease in the activity of the catalyst Ni / SiO2. The weight loss of the catalyst Ni / HSS is 9.1%, which is less than Ni / SiO2. However, no weight loss was found in the catalyst Ni@HSS, indicating that the catalyst Ni@HSS has excellent anti-carbon deposition ability.
[0086] The three different catalysts of Example 1 and Comparative Examples 1-2 were applied to the catalytic pyrolysis process of paint hazardous waste to study the conversion rate of harmful gas formaldehyde. Figure 3 It can be seen that the conversion rate and stability of the catalyst Ni@HSS of the present invention are significantly better than those of the catalyst Ni / HSS of Comparative Example 1 and the catalyst Ni / SiO2 of Comparative Example 2.
Claims
1. A method for preparing an egg yolk-type core-shell catalyst Ni@HSS, characterized in that: The following steps are involved: S1, Preparation of nickel nanoparticles (1) uniformly mixing a nickel source and 1,2-hexadecanediol in a mixed solution of oleic acid, trioctylphosphine and oleylamine, removing water and oxygen in the air in a N2 atmosphere, and obtaining a mixed solution A; the nickel source is nickel acetylacetonate (II), and the concentration in the mixed solution A is 0.05-0.17 mol / L; the concentration of 1,2-hexadecanediol in the mixed solution A is 0.05-0.2 mol / L; the volume ratio of oleic acid, trioctylphosphine and oleylamine is (3-3.5):(4-5):10; (2) heating the mixed solution A to 280-320°C and maintaining the constant temperature for 2-3 hours; then cooling the mixed solution to 80-100°C to obtain a mixed solution B; (3) dissolving the mixed solution B in a solution consisting of oleylamine and borane-tributylamine complex, and keeping the mixture at 90-100°C for 2-3 hours to obtain a mixed solution C; the molar ratio of oleylamine to borane-tributylamine complex is 1:(0.8-1); (4) adding ethanol to precipitate the mixed solution C, separating the solid product, and washing it with cyclohexane; Drying to obtain metal nickel nanoparticles, which are stored under vacuum; S2, Preparation of yolk-type core-shell catalyst Ni@HSS (5) Cyclohexane, Solvay nonionic surfactant and aqueous ammonia solution are stirred and mixed in a reaction flask to obtain a mixed solution D; the metal nickel nanoparticles are added to a mixed solution of tetramethyl orthosilicate, octadecyltrimethoxysilane and cyclohexane, and mixed evenly to obtain a mixture E; in the mixed solution D, the volume ratio of cyclohexane, Solvay nonionic surfactant and aqueous ammonia is (25-30): (8-10): 1; in the mixed solution E, the volume ratio of cyclohexane, tetramethyl orthosilicate and octadecyltrimethoxysilane is (25-30): (1-1.5): 1, and the mass concentration of the metal nickel nanoparticles in the mixed solution E is 1.0-1.5 mol / L; (6) Adding mixture E to mixed solution D, stirring continuously at a temperature of 30 to 40°C for 60 to 90 min; centrifuging to separate the solid, washing with ethanol and vacuum drying; (8) calcining the solid at 500-800° C. for 2-3 hours; (9) reducing the calcined solid in a mixture of H2 and N2 at 800-850°C for 2-3h to obtain the egg yolk-type core-shell catalyst Ni@HSS; The egg yolk-type core-shell catalyst Ni@HSS is used for catalytic pyrolysis of paint hazardous waste.
2. The method for preparing the egg yolk-type core-shell catalyst Ni@HSS according to claim 1, characterized in that: The volume ratio of oleic acid, trioctylphosphine and oleylamine is 3.2:4.6:10; wherein the mass concentration of oleylamine is 60% to 80%.
3. The method for preparing the egg yolk-type core-shell catalyst Ni@HSS according to claim 1, characterized in that: In the mixed solution D, the volume ratio of cyclohexane, Solvay nonionic surfactant and ammonia water is 25:8:1; in the mixed solution E, the volume ratio of cyclohexane, tetramethyl orthosilicate and octadecyltrimethoxysilane is 25:1:
1.
4. The method for preparing the egg yolk-type core-shell catalyst Ni@HSS according to claim 1, characterized in that: In the step (6), the stirring temperature is 30° C. and the stirring time is 60 min. In the step (8), the calcination temperature is 800° C. and the calcination time is 2 h. The heating rate is 2-5° C. / min.
5. The method for preparing the egg yolk-type core-shell catalyst Ni@HSS according to claim 1, characterized in that: In the step (9), the volume fraction of hydrogen in the mixed gas is 5% to 15%; and the flow rate of the mixed gas is 90 to 120 mL / min.
6. The yolk-type core-shell catalyst Ni@HSS prepared according to any one of claims 1 to 5, characterized in that: The hollow silica sphere is used as the shell layer, and nickel nanoparticles are used as the core of the egg yolk-shaped structure in the shell. The nickel nanoparticles are highly dispersed inside the hollow silica microspheres; the hollow silica spheres have mesoporous channels; the mass fraction of nickel is 1 to 20 wt%, the average size of the nickel particles is 2 to 10 nm, the mass percentage of silica is 80 to 99 wt%, and the average diameter of the silica spheres is 5 to 50 nm.
